Preparedness of members of the Indonesian emergency and disaster nurses association - Guruh Suprayitno; Ahsan Ahsan; Karyono Mintaroem (International Journal of Public Health Science (IJPHS), 2020)
Disaster is a global issue all around the world, and Indonesia has shifted its disaster mitigation strategies from emergency response to disaster management preparedness. This research analysed factors influencing the preparedness of members of the Indonesian emergency and disaster association (IEDNA) in the face of natural disasters in Indonesia. This research is analytical-observational with a cross-sectional approach. Sampling was performed on a population of 510 member nurses of the IEDNA by the probability sampling technique. Out of the 510 member nurses of the IEDNA, 107 were enrolled in this research. The Fisher’s exact test results show that knowledge had p= 0.001 (p< 0.05), while facilities and infrastructures availability p= 0.000 (p< 0.05), in their effects on nurse preparedness. The multivariate analysis yielded Exp(B) of 0.022 for knowledge and Exp(B) of 0.003 for facilities and infrastructures availability, while the Nagelkerke’s R-squared obtained was 66%. The variable preparedness was largely good, and there were significant relationships of knowledge and facilities and infrastructures availability to the preparedness of members of the IEDNA. The strongest factor was knowledge.